Learn & Lead study log: innovative pedagogies in management accounting - Ahmad, Emmarelda Maswesi; Hashim, Marshita; Abu Bakar, Najihah; Hashim, Muhamad Ridzuan; Azero, Mohd Afiq (2025)
Today's students learn and engage differently than in the past; they’re more accustomed to quick-paced content like YouTube video tutorials and memes rather than traditional academic content, making lecture formats seem outdated. This phenomenon has led to an ongoing dilemma about how educators can curate learning experiences that impart technical competence and foster critical thinking, engagement and adaptability. Learn & Lead is a study log whose main objective is to compile and showcase some innovative teaching methodologies practiced in the management accounting and control courses. These methods deepen conceptual understanding, enhance student engagement, and bridge the gap between theory and practice. It is everyone’s collective commitment when it comes to creating a joyful and engaging learning experience, even though students may have diverse perspectives and preferences. By collaborating, we can make learning a more engaging and fulfilling educational experience for everyone involved. Learn & Lead study log includes project-based learning, team teaching, technology-enhanced learning, peer review, collaborative teaching with industry professionals, and a digital flipbook. The array of teaching modalities contributes to improving student engagement and critical thinking, enhancing knowledge retention, and supporting effective collaborative teaching methods in addressing today's generation's expectations in the evolving world of AI. The innovative approaches mentioned above, integrated with technology, revolutionise accounting education. It is worth noting that various teaching and learning methods are crucial in preparing future accounting professionals to thrive in a modern and dynamic work environment.